Model of Propagation of Buddhism in Norway - CANDAPANNO (SUKSONG), TINNAWAT (Mahachula Academic Journal, 2025)
This article aims to (1) examine the current situation, problems, causes, obstacles, and needs regarding the propagation of Buddhism in Norway; (2) identify the key factors utilized in the development of Buddhist outreach in Norway; and (3) propose a suitable model for the propagation of Buddhism in Norway. This qualitative research was conducted using in-depth interviews as the data collection tool with 16 participants from three major target groups. The data was analyzed descriptively and analytically. The results showed that the propagation of Buddhism in Norway currently takes place through various approaches, including the establishment of suitable places and environments, the involvement of monks and lay Buddhist missionaries, religious and community activities, environmental preservation, and media outreach. The main factors used for developing propagation strategies include dialogue principles and transformative learning. The research proposes the “NORDLIGHT Model” which consists of eight components: (1) N - Networking Systems, (2) O - Outreach Monks, (3) R - Resilient Laity, (4) D - Dialogue Processes, (5) L - Learning Activities, (6) I - Integrated Media, (7) G - Guided Environments (8) T - Transformative Learning.